Hadis Populer Tentang Ilmu dan Relevansinya dengan Masalah Pendidikan Islam - Irham Irham (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
The Popular Hadith Concerning Knowledge and its Relevance to the Problems of Islamic EducationComprehensive studies on hadiths in terms of sanad, matan, and sharah should be done in order to get a good understanding. This article aims to explain comprehensively a popular hadith as regards the command to study. The takhrij method is used to find the qualities of sanad and matan. Furthermore, it gives sharah on the hadiths especially in the term "ilmu" (knowledge) from the hadith scholars. This article finds that there are variations in explaining the quality of sanad and matan of that hadith. However, in general, the quality of sanad is declared dha'if, and the substance of the matan is declared sahih. Hadith scholars have no problem regarding the law of the dha'if hadith for fadah'il al-'a'mal. Then, the meanings of the word “ilmu” uttered by the scholars are also diverse and have an open character. The diversity of meanings is influenced by the scholars’ different backgrounds. This shows that the meanings of “ilmu” can still develop according to the context of the era. With sharah as such, it can further contribute to addressing the problems of Islamic education in the development of science. Islamic education should act openly and inclusively to carry out scientific studies. Also, it is no longer essential to dichotomize or narrow the meanings of “ilmu”